Faith as an Epistemic Disposition - Byerly, T. Ryan (European journal for philosophy of religion, 2012)
This paper presents and defends a model of religious faith as an epistemic disposition. According to the model, religious faith is a disposition to take certain doxastic attitudes toward propositions of religious significance upon entertaining certain mental states. Three distinct advantages of the model are advanced. First, the model allows for religious faith to explain the presence and epistemic appropriateness of religious belief. Second, the model accommodates a variety of historically significant perspectives concerning the relationships between faith and evidence, faith and volition, and faith and doubt. And, finally, the model offers an appealing account of what unifies religious faith with other kinds of faith.